Production And Antiproliferative Activity Of Various Crude Extract From Lentinus Squarrosulus Mycelium - Rahayu Ahmad; Siti Mariatul Usyida Alias; Aidil Abdul Hamid; Wan Mohtar Wan Yusoff; Endom Ismail; Fauzi Daud (Scholars Academic and Scientific Publishers, 2024)
Non-Indexed Publication